A privacy requirements specification method for Agile Software Development based on exploratory studies - PEIXOTO, Mariana Maia (2021)
SCHUENEMANN, Carla Taciana Lima Lourenço Silva também é conhecida em citações bibliográficas por: SILVA. Carla Taciana Lima Lourenço